The woman in the woods - Connolly, John, 1968- (Connolly, John, 1968- Charlie Parker thriller., 2018)
"From internationally bestselling author and "creative genius who has few equals in either horror fiction or the mystery genre" (New York Journal of Books) comes a gripping thriller starring Private Investigator Charlie Parker. When the body of a woman--who apparently died in childbirth--is discovered, Parker is hired to track down both her identity and her missing child. In the beautiful Maine woods, a partly preserved body is discovered. Investigators realize that the dead young woman gave birth shortly before her death. But there is no sign of a baby. Private detective Charlie Parker is hired by a lawyer to shadow the police investigation and find the infant but Parker is not the only searcher. Someone else is following the trail left by the woman, someone with an interest in much more than a missing child